EFFECT OF BODY CONDITION SCORE ON ESTRUS AND OVARIAN FUNCTION CHARACTERISTICS OF SYNCHRONIZED BEEF-MASTER COWS - Fernando Centurión-Castro (Tropical and Subtropical Agroecosystems, 2013)
The effect of body condition score (BCS) on estrus characteristics and ovarian function was evaluated in 44 synchronized Beef-Master cows. Weaned adult cows in anestrous were grouped according to their BCS as BCS1-2 (n = 13), BCS3-4 (n = 17) and BCS5-6 (n = 14). All cows were synchronized using norgestomet implants plus estradiol valerate for 9 days. The estrus detection began 24 hours after implant removal and it was detected every 6 hours for 72 hours. The time from implant removal to the onset of estrus (TIR) and the duration of estrus were registered. All animals were examined 4 times with a transrectal ultrasound kit to determine the size of the follicles (6 to 9 mm or > 9 mm), the diameter of the largest follicle (DLF), ovulation rate, ovulation rate relative to estrus detection (ORE) and ovulation rate relative to the follicle size (ORF). The effect of BCS on TIR, the duration of the estrus, the number of follicles of size 6 to 9 mm or > 9 mm, and DLF was determined using analysis of variance. The effect of BCS on ovulation rate, ORE and ORF, were determined using Chi-square tests. There were no differences (P> 0.05) between TIR, duration of estrus and follicle sizes between BCS groups. The DLF increased from 9.8 to 12.9 mm, the ovulation rate from 7.7 to 85.7%, the ORE from 0 to 100% and the ORF from 16.7 to 92.9%. In conclusion, under the range of BCS of the synchronized cows, evaluated in this study, the BCS of Beef Master cows did not affect the estrus characteristics; which agree with results observed in other breeds of cattle in the tropics. However, the BCS affect follicle development and ovulation rate.